Discovery and Design of Family VIII Carboxylesterases as Highly Efficient Acyltransferases. Issue 4 (23rd November 2020) - Müller, Henrik; Godehard, Simon P.; Palm, Gottfried J.; Berndt, Leona; Badenhorst, Christoffel P. S.; Becker, Ann‐Kristin; Lammers, Michael; Bornscheuer, Uwe T.
Abstract: Promiscuous acyltransferase activity is the ability of certain hydrolases to preferentially catalyze acyl transfer over hydrolysis, even in bulk water. However, poor enantioselectivity, low transfer efficiency, significant product hydrolysis, and limited substrate scope represent considerable drawbacks for their application. By activity‐based screening of several hydrolases, we identified the family VIII carboxylesterase, EstCE1, as an unprecedentedly efficient acyltransferase. EstCE1 catalyzes the irreversible amidation and carbamoylation of amines in water, which enabled the synthesis of the drug moclobemide from methyl 4‐chlorobenzoate and 4‐(2‐aminoethyl)morpholine (ca. 20 % conversion). We solved the crystal structure of EstCE1 and detailed structure–function analysis revealed a three‐amino acid motif important for promiscuous acyltransferase activity. Introducing this motif into an esterase without acetyltransferase activity transformed a "hydrolase" into an "acyltransferase". Abstract : Promiscuous acyltransferase activity is widespread in family VIII carboxylesterases. A detailed structure–function analysis improved understanding of this remarkable phenomenon and enabled us to rationally transform a hydrolase into an acyltransferase by introducing a single mutation.